Exploring Deep Learning Strategies and Prospective Developments - Sun, Yi (Transactions on Computer Science and Intelligent Systems Research, 2024)
Single Image Super-Resolution (SISR) is a process designed to transform Low-Resolution (LR) images into High-Resolution (HR) counterparts. This technology finds critical applications in various sectors, including gaming, photography, and medical imaging. With the advent and widespread success of deep learning, this approach has been increasingly applied in the realm of SISR. Deep learning-based SISR models are primarily categorized into three types based on their nonlinear module structures: Convolutional Neural Network (CNN)-based models, Generative Adversarial Network (GAN)-based models, and Transformer-based models. This paper presents a comprehensive overview of several emblematic models within each category. An in-depth analysis and comparison of their structural nuances and experimental outcomes are provided. This comparison elucidates how enhancements in network architectures and refined loss function optimizations contribute substantially to advancements in performance. Concluding with an analysis of current models, the paper outlines potential avenues for future exploration and development in the field of SISR, indicating a promising trajectory for further technological advancements.